Health care monitoring and accident tracking system based on location awareness - Sai Nishita, U; Anusha, K; Ramya SriSai, K; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
The main focus of this paper is to design a prototype model such that it embeds different body sensors to measure parameters like body temperature, heart beat rate etc., We used an Arduino UNO board, body sensors like Heartbeat sensor and Temperature sensor to analyze the inputs from the patient’s body and if there are any abnormalities regarding the pulse rate and temperature of the patient the monitoring system would give an alarm and display it on LCD. These processed values are recorded online and stored in the cloud database like Thingspeak and can be accessed through any android mobile or computer systems from any corner of the globe. This system is more useful in transport departments, especially in Buses as a very efficient and dedicated driver healthcare monitoring system. By using this model we can help all drivers who are dedicated to their work and need to be monitored due to their abnormal health conditions. Thus helping them in avoiding fatal accidents and saving the valuable lives of passengers riding along with them in the bus.
Keywords: Arduino UNO Board; Heart Beat Sensor; Temperature Sensor and GPS